In silico structural and functional analysis of Mesorhizobium ACC deaminase. (June 2017) - Pramanik, Krishnendu; Soren, Tithi; Mitra, Soumik; Maiti, Tushar Kanti
Graphical abstract: Highlights: ACC deaminase cleaves ACC into α-ketobutyrate and ammonia. Rhizobial ACC deaminase has reduced the adverse effects of ethylene and triggers the nodulation process. ACC deaminase protein and their corresponding gene sequences of 72 Mesorhizobium spp. have characterized phylogenetically. The acdS proteins of Mesorhizobium spp. have physicochemically, structurally and functionally characterized in silico. It is a thermostable, acidic, globular protein of a molecular mass ranging from 19 to 28 kDa having mainly two conserved domains. Abstract: Nodulation is one of the very important processes of legume plants as it is the initiating event of fixing nitrogen. Although ethylene has essential role in normal plant metabolism but it has also negative impact on plants particularly in nodule formation in legume plants. It is also produced due to a variety of biotic or abiotic stresses. 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase is a rhizobial enzyme which cleaves ACC (immediate precursor of ethylene) into α-ketobutyrate and ammonia. As a result, the level of ethylene from the plant cells is decreased and the negative impact of ethylene on nodule formation is reduced. ACC deaminase is widely studied in several plant growth promoting rhizobacterial (PGPR) strains including many legume nodulating bacteria like Mesorhizobium sp. It is an important symbiotic nitrogen fixer belonging to the class – alphaproteobacteria under the order Rhizobiales. ACC deaminase has positive role in Legume-rhizobium symbiosis. Rhizobial ACC deaminase has the potentiality to reduce the adverse effects of ethylene, thereby triggering the nodulation process. The present study describes an in silico comparative structural (secondary structure prediction, homology modeling) and functional analysis of ACC deaminase from Mesorhizobium spp. to explore physico-chemical properties using a number of bio-computational tools. M. loti was selected as a representative species of Mesorhizobium genera for 3D modelling of ACC deaminase protein. Correlation by the phylogenetic relatedness on the basis of both ACC deaminase enzymes and respective acdS genes of different strains of Mesorhizobium has also studied.